Effect of a hard sublayer on contact interaction and wear behavior of electrodeposited gold-based coatings; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Lyazgin A. О. Aleksandr; Shugurov A. R. Artur Rubinovich; Panin A. V. Alexey Viktorovich; Shesterikov E. V. Evgeny Viktorovich (2014, 2014)
Title screen